Eupalinolide A inhibits cancer progression and induces ferroptosis and apoptosis by targeting the AMPK/mTOR/SCD1 signalling in non-small cell lung cancer - Zhang, Yonghui; Wang, Chen; Zhang, Xiyang; Chen, Dilong; Ren, Zhenni; Yang, Haoning; Wang, Nianhao; Tang, Zumi; Long, Xiling; Zhao, Lilian; Zhou, Na; Zhang, Junqi; et al. (Frontiers in Pharmacology, 2025)
BackgroundNon-small cell lung cancer (NSCLC) is a common malignancy with limited efficacy of established therapies and a poor prognosis that often entails a high financial burden. Eupatorium lindleyanum DC. and its main component Eupalinolide A (EA) are clinically used for the management of chronic tracheitis. Therefore, the aim of this study was to investigate the effects of EA on NSCLC and its underlying molecular mechanisms.MethodsThe effect of EA was assessed on A549 and H1299 tumour cells by flow cytometry, qRT-PCR, western blotting, TUNEL assay, molecular docking, RNA sequencing, non-target metabolomics experimental methodology, and phosphoproteomics to explore the molecular pathways and specific targets. A mouse tumour xenograft model was used to evaluate its effect in vivo.ResultsEA inhibited cell proliferation by arresting the cell cycle at the G2/M phase (increasing the proportion of G2-phase cells in A549 cells from 2.91% to 21.99% and their proportion in H1299 cells from 8.22% to 18.91%). It also promoted apoptosis (increasing the total apoptotic rate in A549 cells from 1.79% to 47.29% and that in H1299 cells from 4.66% to 44.43%) as well as ferroptosis (increasing ROS production by 2.46-fold in A549 cells and by 1.32-fold in H1299 cells). This mechanism was mediated by the modulation of the synthesis of unsaturated fatty acids through the downregulation of stearoyl-CoA desaturase 1 (SCD1) expression, which was reduced by 34% in A549 cells and by 48% in H1299 cells. Notably, the supplementation of oleic acid counteracted the inhibitory effect of EA on cell proliferation and migration. These effects of EA were due to the involvement of the AMPK- mTOR signalling pathway. EA treatment (25 mg/kg) markedly inhibited tumour growth in vivo in a xenograft model; both tumour weight and tumour volume decreased by more than 60% without significantly affecting the body weight of tumour-bearing mice.ConclusionEA inhibited the proliferation and migration of NSCLC cells by the modulation of lipid metabolism through the activation of the ROS-AMPK-mTOR-SCD1 signalling pathway. Therefore, EA might be considered as a promising candidate in the development of therapeutics against NSCLC.